Analysis of Vegetation Structure and Spesies Diversity in the Ranggawulung Urban Forest Area - Oktarina Maulidia; Septian Faris Al Amin; Yossi Dharma; Mhd Muhajir Hasibuan; Shinta Nur Rahmasari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Ranggawulung Urban Forest represents a critical green open space with substantial potential for biodiversity conservation within an urban context. This study aims to characterize the vegetation community structure and assess the conservation status of recorded plant species. Vegetation inventory was conducted using a quantitative approach based on growth stages at two sites: the Urban Forest Block and the Camping Ground Area. The analyses included the Important Value Index (IVI), Shannon-Wiener diversity index (H’), Margalef spesies richness index (Dmg), and evenness index (E). The analysis of species composition and structure revealed distinct patterns in the distribution of the IVI across locations and growth stages. Swietenia mahagoni demonstrated the highest IVI at the seedling growth stage within the urban forest block, as well as at the tree growth stage within the camping ground area. In contrast, within the urban forest block, Maesopsis eminii exhibited the highest IVI at the tree growth stage. Furthermore, in the camping ground area, Cyperus rotundus attained the highest IVI at the seedling and understory vegetation strata. The Shannon-Wiener diversity index (H’) in Ranggawulung Urban Forest indicates that the seedling and understory vegetation strata exhibit higher species diversity compared to the tree strata. The highest H’ value was recorded in the seedling and understory vegetation of the camping ground area (3.5), whereas the lowest was observed in the tree stratum of the camping ground (2.83). The species richness index (Dmg) displayed a similar pattern, with the highest value found in the seedling and understory vegetation of the camping ground (10.42) and the lowest in the tree stratum of the urban forest block (5.22). Meanwhile, the evenness index (E) was relatively high across all categories, peaking in the tree stratum of the urban forest block (0.93), indicating the most balanced distribution of individuals among species in this category. Four species were classified as thteatened acording to the IUCN Red List and CITES Appendices. These findings fulfill the study objectives and underscore the ecological value of the Ranggawulung Urban Forest as a biodiversity refuge, highlighting the need for sustained conservation actions and ecologically informed urban forest management.